Wpływ Połączenia Struktur Mechanicznych na Własności Dynamiczne Agregatu - Cempel, C. (Engineering Transactions, 1973)
The paper examines the receptance of the system composed of elastic elements joined together by means of certain links. It is shown that the links may increase the receptance of the system, especially if the chain system is closed. The important role of flexible links is demonstrated by showing that it may be used to increase, decrease or stop the growth of the receptance.